Piotr Skrzynecki: performer nieustającego święta - Pieniążek, Marek (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
The author of this article highlights the performative aspects of Piotr Skrzynecki’s cabaret and theatre activities, which triggered a special kind of artistic communication with the audience. He places the artist’s profile against the background of communist Poland and the post-transformation cultural reality, emphasising Skrzynecki’s independence from ideological and economic conditions. The creative life of the founder of Piwnica pod Baranami is shown as producing social, communal, and artistic situations of collective celebration. The impact of the cabaret of the Piwnica pod Baranami is analysed by the author as an intentional production of a feedback loop between aesthetic, social, and political groups, establishing a community around the stage event.